Peningkatan Keterampilan Pemasaran Bagi Pelaku UMKM Melalui Pelatihan Digital Marketing, Desain Grafis Berbasis Tiktok Dan Canva Di Desa Taluduyunu - Hamin, Dewi Indrayani; Taan, Hapsawati; Ahmad, Ratna (Celebes Journal of Community Services, 2024)
This service discusses the rapidly increasing number of social media users, this is a very good opportunity for business people to market their products. This community service activity was carried out in Taluduyunu Village, Kec. Buntulia District. Pohuwato, where the residents of the village have several MSME businesses such as handicrafts, various snacks and various other creativity. However, the marketing method for MSME business actors is still carried out offline, only local residents know about and buy products from MSMEs in Taluduyunu Village. Based on these problems, this community service activity was carried out with the aim of providing training on the Effectiveness of Implementing Digital Marketing Models and Graphic Design Based on Tiktok and Canva for Actors in Taluduyunu Village to support product marketing for MSME business actors in Taluduyunu Village. The activity form of this training uses a dialogic collaborative-participatory approach method in the form of lectures, questions and answers and interactive discussions to deliver material, direct practice using a laptop connected to the network. There are 3 stages in training, including: 1) preparation, 2) implementation and 3) reporting. The results of the training show high enthusiasm from the participants, and it is hoped that it can help MSME business people in marketing their products digitally via the TikTok platform, both on other social media and the marketplace.